Evolution after mirror neurons: Tapping the shared manifold through secondary adaptation. (29th April 2014) - Gervais, Matthew M.
Abstract: Cook et al. laudably call for careful comparative research into the development of mirror neurons. However, they do so within an impoverished evolutionary framework that does not clearly distinguish ultimate and proximate causes and their reciprocal relations. As a result, they overlook evidence for the reliable develop of mirror neurons in biological and cultural traits evolved to work through them.